Competition in Interregional Taxation: The Case of Western Coal - Kolstad, Charles D.; Wolak, Frank A. (Journal of Political Economy, 1983)
Markets for many products are dominated by small group of states or countries with a natural advantage in the marketplace because of some initial endowment of resources, favorable climate, or location. The purpose of this paper is to explore how such markets involving a few political jurisdictions interact noncooperatively. We examine how such a market might be structured and operate and the extent of monopoly rent that can be extracted in the absence of collusion. We answer these questions for an empirically estimated model of western U.S. coal in which two states (Montana and Wyoming) dominate production. We demonstrate that in this market the amount of rent that can be extracted is greatly reduced through competition (relative to a cartel). Nevertheless, even with two producing states competing against each other, significant rents can be captured–significant enough to refute the contention that little rent can accrue without a cartel.